VAT/GST harmonisation challenges for digital assets such as bitcoin and NFTs in the EU following Case C-264/14 (Skatteverket v David Hedqist) - Stephanie Ness (International Cybersecurity Law Review, 2024)
Abstract The verdict in the case of Skatteverket v. David Hedqvist (Kokott, Advocate General (2015) Opinion delivered on 16 July 2015, Case C-264/14. ECLI:EU:C:2015:498. Available via TandF Online. https://doi.org/10.1080/20488432.2015.1096631 .) is crucial for understanding how the EU treats virtual currencies, such as Bitcoin, in terms of Value-added Tax (VAT). This case involved the Swedish citizen David Hedqist who was seeking clarity from the Swedish Tax Authority Skatteverket on exchanging money for Bitcoins. The case set a precedent exempting such services from VAT under the EU’s VAT Directive (Council Directive 2006/112/EC (2006) On the common system of value added tax. OJ L347. Available via EUR-Lex. https://eur-lex.europa.eu/legal-content/EN/ALL/?uri=CELEX:32006L0112 . Accessed 3 January 2024.). Specifically, Article 135(1)(e) of the EU’s VAT Directive excludes those transactions from VAT that include money-related transactions, that include deals or negotiations about different kinds of money, including cash and coins that are officially legal tender, i.e., used for buying things, except for collectable items like special coins or notes that people collect but do not use as a means of payment. Skatteverket (Kokott, Advocate General (2015) Opinion delivered on 16 July 2015, Case C-264/14. ECLI:EU:C:2015:498. Available via TandF Online. https://doi.org/10.1080/20488432.2015.1096631 .) clarified that cash transactions are not subject to VAT, even though they are considered services for VAT purposes. Despite this clarity, the evolving landscape of digital assets’ uniqueness, including Non-Fungible Tokens (Alawadhi KM, Alshamali N (2022) NFTs Emergence in Financial Markets and their Correlation with DeFis and Cryptocurrencies. Applied Economics and Finance 9:108. https://doi.org/10.11114/aef.v9i1.5444 . Available at CORE. https://core.ac.uk/download/pdf/524752899.pdf . Accessed 3 January 2024.), continues to challenge VAT frameworks across member states. Using insights from the European Commission’s Working Paper 1060, this article advocates for a unified approach tailored to digital and crypto services, addressing complexities in NFT taxation to reduce uncertainty and foster market cohesion. The findings highlight the importance of legislative changes and increased cross-border collaboration, as well as provide recommendations for policymakers and stakeholders in the digital finance and platform sector (European Commission (2024) Working Paper 1060. Available at: https://ec.europa.eu/info/publications/working-paper-1060_en . Accessed 3 March 2024.). By proposing strategic harmonisation of VAT enforcement, the research helps to improve tax compliance and support long-term growth in the EU’s digital market (Cappai M (2023) The role of private and public regulation in the case study of crypto-assets: The Italian move towards participatory regulation. Computer Law & Security Review 49:105831. Available at: https://www.sciencedirect.com/journal/computer-law-and-security-review/vol/49/suppl/C .; Hasa J (2021) Digitaalisten palvelujen rajat ylittävä kuluttajakauppa ja laajeneva arvonlisäveron erityisjärjestelmä. Licentiate thesis. University of Lapland, Faculty of Law. Available at: https://lauda.ulapland.fi/bitstream/handle/10024/64771/Hasa_Juho.pdf?sequence=1 . Accessed 1 March 2024.).